State pensions and the well-being of the elderly in the UK - James Banks; Richard Blundell; Carl Emmerson; Zoë Oldfield (Institute for Fiscal Studies (IFS), 2006)
This paper presents the trends seen over the last quarter of the 20th Century in various indicators of the well-being of the elderly alongside those seen for the young. Specifically we look at measures of both the level and distribution of income and expenditure, and self-reported measures of life satisfaction and health. We then exploit the substantial reforms to the UK pension system over this period to examine the impact of reforms to state pensions on these outcomes. We find that increases in the generosity of state pensions have led to increased incomes of the elderly and reductions in measures of both relative and absolute income poverty. We also find that increased state pensions have led to increased expenditure by the elderly. It is perhaps not surprising that in the UK the reforms to the generosity of state pensions have affected outcomes among the elderly (instead of being fully offset by individuals when they were younger) given that often very little (pre-retirement) notice was given, and that some of the reforms were of a substantial magnitude.
Keywords: 330